The Analysis Of Translation Strategies Used in English-Indonesian Signages at Bali Zoo - Atma Novia Lestari; Ni Made Verayanti Utam; I Dewa Ayu Devi Maharani Santika (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
Abstract When it comes to translation there are several things that need to be considered by translator such as the equivalence of messages, grammatical structures and culture value between two languages. Hence why, this is the reason to raise this topic as a study because English is not a native language of Indonesian. This study was focused on to find out the translation strategies which used in English-Indonesian signages at Bali Zoo which located at Gianyar Regency, Bali Province. The translation strategies theory which proposed by Newmark (1988) was used in order to answer the problem of this study. The qualitative method was used in this study. The result showed that there are 5 types of translation strategies can be found based on 22 data which are 7 literal translation (31.81%), 2 faithful translation (9.09%), 2 semantics translation (9.09%), 7 free translation (31.81%) and 4 communicative translation (18.18%). It can be indicated that literal and free translation are the most dominant translation strategies that had been found with each of 7 data. Then followed by communicative translation by 4 data, faithful and semantics translation with each of 2 data. Keywords: translation strategy, signage, bali zoo.